Analytical modelling of protective headgear for soccer players - Mohd Hasnun Ariff, Hassan; Zahari, Taha (Centre for Advanced Research on Energy (CARe), 2017)
Studies have shown that heading in soccer might result in drain trauma injury this study proposes an analytical model thati provides linear acceleration of both skull and brain during soccer hall heading when wearing protective headgear to evaluate the effieacy of the headgear. Each component in the model (the soccer ball headgear. skull, arid brain) is represented by a mass, a spring and a damper. The simulation shows that a commercial soccer beudgear was unable to reduce the head acceleration due to soccer heading, this model shows a potential as an evaluation tool for soccer headgear.